The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acscatal.1c00950
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Isolated Rhodium Cations by MFI Zeolite for Heterogeneous Methanol Carbonylation

Abstract: Methanol carbonylation is known as a classic reaction of homogeneous catalysis with large-scale industrial applications. The heterogenization of homogeneous catalysts is being pursued to address the issues of catalyst deactivation and separation encountered in homogeneous systems. Herein, we report the strategy of stabilizing isolated rhodium cations by MFI zeolite to construct highly active Rh@MFI zeolite catalysts for heterogeneous methanol carbonylation. The formation of a zeolite-stabilized [Rh­(CO)2I2] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…The confined environment of zeolites could provide the spatial restriction for the small metal entities, which can improve the metal stability against sintering and leaching of active metal species during catalysis. , Additionally, such a successful encapsulation can afford site proximity between metal and acid sites, which could improve catalytic performance owing to providing synergistic effects between the different functional sites. The impregnation and ion-exchange methods are traditional approaches widely employed for achieving metal species highly dispersed into zeolite cavities. However, both methods have their own limits and are either not suitable or effective for the metal encapsulation into small-pore zeolites (8-member ring zeolite, e g., LTA zeolite, 0.42 nm in aperture size) and medium-pore zeolites (10-member ring zeolite, e g., MFI zeolite, 0.55 nm in aperture size) . Notably, previous studies have shown some successful examples of metal encapsulation into MFI zeolites via different approaches. However, most MFI zeolites in those cases were related with purely siliceous MFI zeolites (silicate-1) and TS-1. Recently, a seed-assistant hydrothermal method has been reported for the synthesis of ZSM-5 zeolite-encapsulated metal or metal oxide .…”
Section: Introductionmentioning
confidence: 99%
“…The confined environment of zeolites could provide the spatial restriction for the small metal entities, which can improve the metal stability against sintering and leaching of active metal species during catalysis. , Additionally, such a successful encapsulation can afford site proximity between metal and acid sites, which could improve catalytic performance owing to providing synergistic effects between the different functional sites. The impregnation and ion-exchange methods are traditional approaches widely employed for achieving metal species highly dispersed into zeolite cavities. However, both methods have their own limits and are either not suitable or effective for the metal encapsulation into small-pore zeolites (8-member ring zeolite, e g., LTA zeolite, 0.42 nm in aperture size) and medium-pore zeolites (10-member ring zeolite, e g., MFI zeolite, 0.55 nm in aperture size) . Notably, previous studies have shown some successful examples of metal encapsulation into MFI zeolites via different approaches. However, most MFI zeolites in those cases were related with purely siliceous MFI zeolites (silicate-1) and TS-1. Recently, a seed-assistant hydrothermal method has been reported for the synthesis of ZSM-5 zeolite-encapsulated metal or metal oxide .…”
Section: Introductionmentioning
confidence: 99%
“…The sizes, shapes, and oxidation states of active sites in heterogeneous catalysts change dynamically depending on the reaction temperature, atmosphere, and adsorbent. Owing to recent progress in in situ / operando spectroscopic techniques and density functional theory (DFT) calculations, structural changes in the active species during catalytic cycles have been observed under the working states, leading to a molecular-scale understanding of the reaction mechanism. The molecular-level understanding of heterogeneous catalysis is reported to be less than that of homogeneous catalysis because of the nonuniformity in the structure of the solid surfaces. Well-defined metal complexes or clusters in zeolites are rare examples of structurally uniform heterogeneous catalysts. Rhodium complexes and clusters anchored in zeolites are among the successful examples of well-defined active species. Reversible changes in their oxidation states and nuclearities (isolated complexes ↔ metal clusters) depending on the reaction conditions have been characterized using in situ / operando spectroscopic techniques. Fang et al investigated the dynamic structural evolution of Rh species in zeolites using in situ infrared (IR) and X-ray absorption spectroscopy (XAS) and revealed that [Rh­(CO) 2 ] + complexes anchored at zeolitic anion sites were reversibly converted into Rh 4 (CO) 12 and Rh 6 (CO) 16 clusters depending on the reaction temperature under a flow of CO + H 2 O or CO 2 + H 2 . , Amiridis and co-workers conducted XAS, high-resolution scanning transmission electron microscopy (HRSTEM), IR, and DFT calculations to clarify the detailed structure of isolated [Rh­(NO) 2 ] + complexes in the zeolite and their catalysis for the hydrogenation and dimerization of hydrocarbons . Although previous studies have focused on the in situ / operando characterization of well-defined Rh species under steady-state conditions, only a few studies have reported unsteady-state catalysis of anchored Rh complexes driven by their reversible structural changes …”
Section: Introductionmentioning
confidence: 99%
“…Heterogenization of homogeneous catalysts is a great challenge, but it plays a significant role in the field of catalysis and industrial production. Homogeneous catalysts have obvious advantages of fast mass transfer and high conversion rates, but catalyst separation and reuse are difficult. , While heterogeneous catalysts are convenient for reuse, they usually have uneven active sites and low activity . Heterogenization of homogeneous catalysts is an attractive approach to enable the catalyst to be easily separated for reuse and exhibit excellent catalytic activity .…”
Section: Introductionmentioning
confidence: 99%